2014
DOI: 10.1007/s00464-014-3677-5
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared fluorescent cholangiography facilitates identification of biliary anatomy during laparoscopic cholecystectomy

Abstract: BACKGROUND Intraoperative cholangiography (IOC) is the current gold standard for biliary imaging during laparoscopic cholecystectomy (LC). However, utilization of IOC remains low. Near Infrared Fluorescence Cholangiography (NIRF-C) is a novel, noninvasive method for real-time, intraoperative biliary mapping. Our aims were to assess the safety and efficacy of NIRF-C for identification of biliary anatomy during LC. METHODS Patients were administered indocyanine green (ICG) prior to surgery. NIRF-C was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
115
2
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(124 citation statements)
references
References 33 publications
2
115
2
5
Order By: Relevance
“…The mean interval between the ICG injection and the first obtained fluorescent cholangiography in our study (39 ± 4 min) was similar to what has been reported previously (range 33-74 min) [4][5][6]. In our study, the interval between the ICG injection and the first obtained fluorescent cholangiography was not associated with detectability of the biliary structures; however, the fact that the gallbladder could be identified under fluorescent cholangiography before dissection in Calot's triangle in all our patients indicated that the interval between the ICG injection and the first obtained fluorescent cholangiography was sufficient for us to start assessing the detectability of the biliary structures during SILC.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The mean interval between the ICG injection and the first obtained fluorescent cholangiography in our study (39 ± 4 min) was similar to what has been reported previously (range 33-74 min) [4][5][6]. In our study, the interval between the ICG injection and the first obtained fluorescent cholangiography was not associated with detectability of the biliary structures; however, the fact that the gallbladder could be identified under fluorescent cholangiography before dissection in Calot's triangle in all our patients indicated that the interval between the ICG injection and the first obtained fluorescent cholangiography was sufficient for us to start assessing the detectability of the biliary structures during SILC.…”
Section: Discussionsupporting
confidence: 91%
“…The clinical value of fluorescent cholangiography during conventional laparoscopic cholecystectomy is becoming clearer [1][2][3][4][5]. High detectability of biliary structures during conventional laparoscopic cholecystectomy has established the usefulness of fluorescent cholangiography.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though the role of routine ICGC on common bile duct injury on a larger scale has yet to be evaluated, surgeons using this technology have demonstrated that it is safe with no ductal injuries reported in their clinical practices (38). Several studies have demonstrated equal or improved visualization of biliary anatomy and anatomic variants with ICGC, without the added time and morbidity associated with traditional intra-operative cholangiography (39,40). In addition, the conversion to open procedures has been decreased with the utilization of this technology (41).…”
Section: Indocyanine Green Cholangiographymentioning
confidence: 99%
“…If it is rather short, or if it is absent entirely, ductal division without cholangiography guidance can be hazardous to the donor and may render recipient ductal reconstruction difficult and suboptimal. Near-infrared fluorescence cholangiography may be helpful for more precise determination of the line of division of the right hepatic duct [3]. As indocyanine green is excreted into the main ducts, fluorescence makes the ducts more visible, so the surgeon has a better picture of the biliary anatomy.…”
mentioning
confidence: 99%